The Study Of Relationship Between Emotional Labor And Different Level Of Workplace Aggression Of Front-Line Staff Of Hotel Industries In Penang Island - Harianto, Harianto (2011)

(untitled)
The purpose of this study is to investigate the relationship between emotional labor and different level of workplace aggression of front-line staff of hotel industries in Penang Island.